Intersectional identity of 13th-century Javanese women in the novel "Tutur Dedes" - Budiyanto, Dwi; Kusmarwanti, Kusmarwanti; Liliani, Else; Sayuti, Suminto A. (LITERA, 2024)
Within thirteenth-century Javanese tradition in Southeast Asia, women are frequently marginalized. Women who had significant influence were often omitted from historical records, such as Ken Dedes. Her tale is exclusively documented in the book of Pararaton. Dedes is seen as a significant woman who bore the ruling dynasty in Java. Modern Indonesian literature depict Dedes in different ways, offering varied interpretations of her character. This study seeks to analyze the intersectional identity of Ken Dedes in the novel Tutur Dedes: Doa & Kutukan by Amalia Yunus (2022) because of the intricate nature of her identity. The data consist of narrative elements such as tale sequences, characters, settings, themes, and other literary devices sourced from data repositories relevant to the research issue. The data were collected using reading and note-taking methods. Additionally, it was qualitatively analyzed via the lens of Kimberle Crenshaw's (1989) intersectionality approach. The results indicate that Dedes is shaped by various intersecting identities: education for an educated identity, biological physique for beauty and sexuality, high social status for respectability and knowledge access, religion for personal integrity, gender for the role of a mother, and political position for influence and network power. Each component category interacts to shape, reinforce, and internalize Dedes' identity and self as an educated woman in the thirteenth century, who wields significant influence and can overcome the oppression she faces. This study emphasises the importance of viewing women's identities as a cohesive whole rather than in fragmented elements. Javanese women were well educated and engaged in many facets of society in the thirteenth century.